Pelaksanaan Cangkurah Expo 2024; 498 Tahun Kota Banjarmasin Dalam Bingkai Poto Dan Lukisan - syafril, syafril; Selvanus, Selvanus; Fahmi, Muhammad; Fadilah, Neti Rosiana (JCSE: Journal of Community Service and Empowerment, 2025)
This Community Service Activity (PKM) is one of the obligations to implement the Tridharma of Higher Education, namely; Carrying out teaching, conducting scientific research and community service for a lecturer.  This Community Service Activity was carried out thanks to collaboration between the Regional Government, Professionals and Academics.  This activity aims to increase the income of creative economy actors, especially in the fields of photography and painting, which have so far received little attention.  This service activity is held using the method of holding exhibitions, workshops, talk shows and exhibitions in the field of photography and painting to advance the creative photography and painting industry.  The results of the activities have had a very positive impact on creative economy actors in the fields of photography, painting and culinary by generating significant income during the exhibition period starting from 20-29 December 2024. Creative economy activities must receive attention because they are in direct contact with MSME actors.